Unraveling the phenomenon of construction labor productivity: a cutting-edge bibliometric analysis - Revianty Nurmeyliandari Nurhendi; Mukhlis Nahriri Bastama; Muhamad Azry Khory; Muhamad Razuhanafi Mat Yazid (Penerbit Universiti Kebangsaan Malaysia, 2024)
Construction Labor Productivity (CLP) is a critical factor in the construction industry that can significantly influence the success of a project. The lack of comprehensive knowledge and proficiency in CLP and its substantial impact on project outcomes is a significant concern. CLP is a highly effective concept that can significantly improve the overall efficiency of construction projects. While it has received considerable academic attention, it is still relatively underutilized in practice. This academic analysis aims to identify trends within the CLP as revealed by a comprehensive review of existing academic research. A bibliometric analysis, complemented by a descriptive quantitative statistical methodology, was utilized to evaluate the performance metrics and delineate the thematic landscape about the subject matter of CLP. Employing distinct keywords pertinent to the CLP phenomenon and applying specific criteria for metadata exploration facilitated a comprehensive search within the Scopus and Web of Science databases. The PRISMA flowchart was employed as a systematic approach for the identification, screening, and eligibility evaluation of metadata to be incorporated into this study. The study highlights growing CLP research, led by the US and the University of Alberta. Key trends include “improvement” and “construction equipment,” with future focus on “machine learning” and “artificial intelligence.” Despite their potential, data challenges limit their use. More research is needed in developing countries to enhance construction labor productivity.